1996
DOI: 10.1017/s0890037x00040550
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Use of the “Bialaphos Genes” for Improving Bioherbicide Efficacy

Abstract: We are studying the possibility of altering the virulence and host range of a phytopathogen by transferring and expressing certain genes from the soil-dwelling saprophyte, Streptomyces hygroscopicus, in a plant pathogen model, Xanthomonas campestris pv. campestris (XCC). The genes, referred to herein as the “bialaphos genes,” encode the production of bialaphos, a potent glutamine-synthetase-inhibiting herbicide. This cluster of genes was originally isolated from several biosynthetically blocked mutants of S. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, most studies and discussions have focused on the enhancement of virulence (Amsellem et al 2002;Gressel 2002;Vurro et al 2001), which has primarily focused on the enhancement of the production of an enzyme or toxin (Greaves et al 1989;Gressel 2002). In addition, a pathogenic or nonpathogenic microbe could be used to colonize a weed and deliver a herbicidal molecule (Charudattan et al 1996). Fungi such as Fusarium spp.…”
Section: Genetic Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies and discussions have focused on the enhancement of virulence (Amsellem et al 2002;Gressel 2002;Vurro et al 2001), which has primarily focused on the enhancement of the production of an enzyme or toxin (Greaves et al 1989;Gressel 2002). In addition, a pathogenic or nonpathogenic microbe could be used to colonize a weed and deliver a herbicidal molecule (Charudattan et al 1996). Fungi such as Fusarium spp.…”
Section: Genetic Enhancementmentioning
confidence: 99%
“…Only a few examples of microbes genetically engineered for enhanced bioherbicide potential have been reported. Charudattan et al (1996) investigated the use of generating enhanced Xanthomonas isolates by transformation with genes encoding bialaphos and found that transgenic isolates were more virulent than the wild type. A number of groups have studied NEP1, a gene encoding ''necrosis eliciting protein'' (Amsellem et al 2002;Bailey et al 1997Bailey et al , 2000, and this model has proven valuable.…”
Section: Genetic Enhancementmentioning
confidence: 99%
“…For example, Tiourebev et al [111] have attempted a new approach to enhance virulence of a microbial agent by selecting strains that are capable of producing high levels of amino acids that can suppress the growth and development of plants causing leaf distortion, loss of apical dominance and stunted growth. Charudattan et al [112] altered the virulence and host range of a bacterium by inserting genes, which encoded for the production of bialaphos, a glutamine-synthetase inhibiting herbicide. Alteration of such bacterial genes could produce overall increases in virulence, host range or other related traits.…”
Section: Future Trends Of Mycoherbicides In Aquatic Weed Controlmentioning
confidence: 99%
“…Work on the use of bialaphos genes is being performed Volume 15, Issue 4 (October-December) 2001 by transforming Xanthomonas campestris pv. campestris with bialaphos genes (Charudattan et al 1996). Alteration of such bacterial genes could produce overall increases in virulence, host range, or other related traits.…”
Section: The Use Of Pathogens As Bioherbicidesmentioning
confidence: 99%